Efficient Strategies for Wireless Systems - Bhargava, Kanav (Journal of Research in Science and Engineering, 2025)
Wireless Sensor Networks (WSNs) are cutting-edge technology with vast potential for future applications. Sensor nodes in these networks are limited by energy constraints, relying on batteries with restricted capacity that can impact their longevity and mobility. To combat this issue, energy harvesting technology offers a solution by replenishing node batteries through environmental resources. This study delves into the concept of energy harvesting technology (EH) and its application in Energy-Harvesting for Wireless Sensor Networks (EH-WSN). Various strategies from existing literature are evaluated for reducing energy consumption in energy harvesting sensor networks. The review analyzes protocol design approaches and operational principles, as well as highlighting the strengths, weaknesses, and potential research avenues in this field.